2011
DOI: 10.1016/j.aller.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of physical exercise on antioxidant status in asthmatic children

Abstract: Structured exercise programme in asthmatic children resulted in better lung function, which may be attributed to its effect on antioxidant status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 28 publications
4
84
0
6
Order By: Relevance
“…These findings were in agreement with several previous studies (Goon et al, 2009;Huang et al, 2014;Onur et al, 2011;Wadiah et al, 2015). Huang et al (2014) reported that there was no significant change in GPx level at week 8 but there was a significant increase in GPx activity at week 12.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…These findings were in agreement with several previous studies (Goon et al, 2009;Huang et al, 2014;Onur et al, 2011;Wadiah et al, 2015). Huang et al (2014) reported that there was no significant change in GPx level at week 8 but there was a significant increase in GPx activity at week 12.…”
supporting
confidence: 94%
“…Performing higher physical activity or aerobic exercise alone has been proven to increase cardiovascular fitness (Kemmler et al, 2004;Suter et al, 1994) and improve lipid profile (Isler et al, 2001;Kannan et al, 2014). Performing exercise can also improve antioxidant adaptation (Goon et al, 2009;Onur et al, 2011) and reduce oxidative damage markers (Goon et al, 2009). In order to transform exercise into a top priority, the exercise chosen should be enjoyable and something that can be maintained so that it can be turned into a healthy lifestyle later (American College of Sports Medicine, 2009;Lavie, 2007).…”
mentioning
confidence: 99%
“…At baseline, percentage of predicted lung function ((FEV 1 and forced vital capacity (FVC)) was reduced in the vast majority of the studies (online supplementary Web only file 1). FEV 1 could be improved in 3 of 20 studies by exercise training,27 42 44 whereas the FVC improved in only two studies 27 42. Peak expiratory flow (PEF) was the main lung function parameter that was improved, albeit mildly, by exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Onur et al 42 found that markers of oxidative stress in blood serum (malondialdehyde, total nitric oxide (NO)) were reduced in children with asthma after exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Na asma, o efeito anti-inflamatório do exercício tem sido muito menos explorado, porém alguns estudos observaram que a prática regular de exercício físico pode reduzir o estresse oxidativo (Onur et al, 2011), o broncoespasmo induzido pelo exercício e o uso de corticosteroides (Neder et al, 1999;Fanelli et al 2007). Apesar destes estudos sugerirem indiretamente uma possível redução da inflamação pulmonar conhecemos apenas quatro estudos que avaliaram o efeito do treinamento físico na resposta inflamatória em pacientes asmáticos e seus resultados podem ser considerados controversos.…”
Section: Efeito Anti-inflamatório Do Exercício E O Seu Papel Na Asmaunclassified